Recent Emerging Trend in Stem Cell Therapy Risk Factors - Pourjabbar, Bahareh; Shams, Forough; Moghadam, Maryam; Ahani-Nahayati, Milad; Azari, Arezo; Sefat, Farshid; Keshel, Saeed H. (Current Stem Cell Research & Therapy, 2023)
Different types of stem cells have remarkable characteristics such as high proliferation rate, multi/pluripotency, self-renewal, and broad differentiation that can effectively treat diseases, cancers, and damage. Despite abundant therapeutic applications of stem cells in medical science, numerous risks threaten stem cell transplantation. Tumor development, immune response, cellular senescence, dosage effects, and administration timing are critical risks that should be considered in stem cell therapy. Hence, an investigation of possible risks is required before utilizing stem cell-based medicinal products in the clinical phase and human trials. This review aims to survey the literature and perspectives on the advantages and risks associated with pluripotent and multipotent stem cells.
Keywords: risk factors